Analysis of Verbal and Nonverbal Communication in Grade 11 EFL Classroom Interaction - Adel Pinola Br Ginting; Dinda Khairani Pratiwi; Dinda Nurul Fadillah; Nurfarah Nurfarah; Naufal Nasution (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2025)
The aim of this study is to analyze verbal and non-verbal communication in an English as a Foreign Language (EFL) classroom by using the Sinclair and Coulthard (1975) model of classroom discourse. Although many studies have examined verbal interaction in EFL classrooms, few have discussed how verbal and non-verbal communication work together to support effective learning. To fill this gap, this research focuses on identifying the types and frequency of verbal and non-verbal communication used by the teacher and students during classroom interaction. This study used a descriptive qualitative method. The data were taken from an 80-minute video recording of an eleventh-grade English class at MAS Darul Quran. The recording was transcribed and analyzed based on Sinclair and Coulthard’s framework, which includes three main levels: Exchange (Informing, Directive, Question–Answer), Move (Initiation, Response, Feedback), and Act (Questioning, Explaining, Agreeing, Refusing, Revising, Appraising). The findings show that the classroom interaction was mainly teacher-centered. The teacher dominated the talk through Initiation moves, mostly in the form of questions, explanations, and instructions, while students gave short and simple responses. Feedback was used less often and mostly as short praise or confirmation. The teacher also used various non-verbal behaviors such as gestures, eye contact, movement, and changes in voice tone to direct attention and motivate students. The results suggest that combining verbal and non-verbal strategies can create a more interactive and engaging classroom atmosphere that supports student participation and understanding.